Neurological complications after gamma-knife radiosurgery for hypothalamic hamartoma. (September 2016) - Butragueño Laiseca, Laura; Oikonomopoulou, Niki; Miranda Herrero, María Concepción; Barredo Valderrama, Estíbaliz; Vázquez López, María; Jiménez de Domingo, Ana; Aguado del Hoyo, Alejandra; García-Leal, Roberto; Meiriño, Rosa M.
Abstract: Background: The Gamma-knife technique is a safe and effective option for the treatment of hypothalamic hamartomas that produce epileptic seizures refractory to medical treatment and/or serious behavioral disorders. After this type of radiosurgery, an adequate symptomatic control is normally achieved, with notable decrease or even disappearance of the seizures. Radiological changes, such as a decrease in the size of the tumor or adjacent edema secondary to non-necrotizing radioinduced inflammatory reaction are unusual consequences. Side effects and neurological complications are also rare events. Case presentation: This report describes an unusual case of complete radiological resolution of a hypothalamic hamartoma as well as neurological complications after Gamma-knife surgery (receiving 13 Gy to the 85% isodose line, 1 cm 3 of tumor volume) in a 8-year-old boy who suffered from severe refractory seizures. After radiosurgery, the patient experienced a notable improvement in his symptoms, achieving seizure cessation within 3 months. However, 4 months after the procedure he presented drowsiness, fever and decreased level of consciousness due to a direct effect on the hypothalamus with local and regional edema secondary to the radiosurgery that was performed. He was successfully treated with corticosteroids (with a total duration of 11 months), and twelve months after the surgery, complete disappearance of both the nodular lesion and the secondary edema was observed. The patient remains seizure-free in the last 16 months, with remarkable changes in his behavior. Conclusions: The present case shows that complete radiological resolution of a hypothalamic hamartoma after Gamma-knife technique is unusual but possible, without long-term neurological consequences. Nevertheless, despite its low incidence, if a patient presents neurological symptoms, primarily during the first year after intervention, possible complications of this type of surgery must be taken into account. Highlights: The Gamma-knife technique is an effective option for the treatment of hypothalamic hamartomas. Radiological changes, side effects and neurological complications are uncommon consequences. We report radiological resolution of a hypothalamic hamartoma as well as neurological complications after Gamma-knife surgery. If a patient presents neurological symptoms, possible complications of this type of surgery must be taken into account.